2016
DOI: 10.1007/s10529-016-2144-x
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of chitosan/BmNPV bacmid DNA nanocomplex as transfection reagent of recombinant protein expression in silkworm larvae

Abstract: This is the first finding that chitosan/BmNPV bacmid DNA nanocomplexes can rival the performance of commercially available transfection reagents for the expression of recombinant proteins in Bm5 cells and silkworm larvae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Recently, "trained immunity" has been evidenced in invertebrate innate immune systems, such as those of shrimp 24,45 . Several studies have demonstrated that shrimp immune priming with inactivated pathogenic bacteria (e.g., Vibrio harveyi, V. alginolyticus, and V. anguillarum) could protect them from vibriosis 46,47 . In addition, evidence has indicated an improved survival rate in shrimp primed with killed or attenuated WSSV 24,48 or with WSSV structural subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, "trained immunity" has been evidenced in invertebrate innate immune systems, such as those of shrimp 24,45 . Several studies have demonstrated that shrimp immune priming with inactivated pathogenic bacteria (e.g., Vibrio harveyi, V. alginolyticus, and V. anguillarum) could protect them from vibriosis 46,47 . In addition, evidence has indicated an improved survival rate in shrimp primed with killed or attenuated WSSV 24,48 or with WSSV structural subunits.…”
Section: Discussionmentioning
confidence: 99%
“…All the sequences were confirmed directly by DNA sequencing. The corresponding bacmid was subsequently transfected into either cultured Bm5 cells or silkworm fifth instar larvae using 1,2-dimyristyloxypropyl-3-dimethyl-hydroxy ethyl ammonium bromide and cholesterol (DMRIE-C, ThermoFisher Scientific K. K., Tokyo, Japan) transfection reagents (2 μg/1 μL bacmid DNA) or chitosan/bacmid system to obtain recombinant baculoviruses according to the protocols established previously ( Kato et al, 2016 ; Xu et al, 2019 ). The series infection method obtained the stock of high titer viruses employed for infecting silkworm cells and larvae.…”
Section: Methodsmentioning
confidence: 99%
“…The positive recombinant plasmid pFB-MjgC1qR-His was used to transform E. coli BmDH10Bac for the generation of a recombinant Bombyx mori nucleopolyhedrovirus (BmNPV) bacmid 62 . The bacmid was then transfected into silkworm larvae.…”
Section: Methodsmentioning
confidence: 99%